Counseling and management of patients requesting subcutaneous contraceptive implants: proposal for a decisional algorithm. (July 2014) - Guida, Maurizio; Visconti, Federica; Cibarelli, Francesca; Granozio, Giovanni; Troisi, Jacopo; Martini, Ellis; Nappi, Rossella
Abstract Despite the easy access to contraception today, the rate of unintended pregnancies is still high because of scarce education among women on the methods available and of non-adherence to indications or discontinuation of the contraceptive method chosen. Adherence to contraception can be implemented through counseling programs intended to provide potential users with information regarding all contraceptive options available and to address women's concerns in line with their lifestyle, health status, family planning, and expectations. In here, we evaluate a multi-step decisional path in contraceptive counseling, with specific focus on potential users of long-acting release contraception etonorgestrel. We propose an algorithm about the management of possible issues associated with the use of subcutaneous contraceptive implant, with a special focus on eventual changes in bleeding patterns. We hope our experience may help out health-care providers (HCPs) to provide a brief but comprehensive counseling in family planning, including non-oral routes of contraceptive hormones. Indeed, we believe that a shared and informed contraceptive choice is essential to overcome eventual side-effects and to improve compliance, rate of continuation and satisfaction, especially with novel routes of administration.